PROSTHETIC REHABILITATION OF A PATIENT WITH ACQUIRED ORBITAL DEFECT USING SPECTACLE RETAINED ORBITAL PROSTHESIS – A CASE REPORT - Shagun Acharya,; Reecha Gupta,; Udfer Hameed,; Shivani Jandiyal,; Nitin Gautam,; Paaras Kotwal, (IJRDO-Journal of Applied Science, 2025)
Rehabilitation of facial defects is a complex task, which requires an individualized design of prosthesis for each patient. Fabrication of orofacial prosthesis is highly technique sensitive procedure thus visual assessment alone may not always be accurate.  Various treatment modalities are available, one of which is the use of implants. Although implant-supported orbital prosthesis has a superior outcome, it may not be acceptable to all the patients due to its higher cost. Prosthetic rehabilitation is the treatment of choice when surgical reconstructive procedure does not show satisfactory results. Multidisciplinary management and team approach are essential in delivering an accurate and effective rehabilitation for the patient. The present article describes a simplified technique for the fabrication of an acrylic orbital prosthesis to achieve ideal fit and aesthetics